Persepsi dan Motivasi Petani Terhadap Panduan Budidaya GTP (Good Tobacco Practices) di Desa Sumber Pinang Kecamatan Pakusari Kabupaten Jember - Azizah Azizah; Ebban Bagus Kuntadi (UPT Penerbitan Universitas Jember, 2018)
Tobacco is a plantation crop that is widely cultivated in Indonesia because of its large market share both in domestic and abroad. Jember Regency is one of the central area of tobacco production voor-oogst kasturi and besuki Na Oogst. Tobacco voor-oogst kasturi is typical tobacco and only produced in area of Jember Regency and surrounding, this type of tobacco is widely cultivated by farmers in Sumber Pinang, Pakusari, Jember. Kasturi tobacco cultivation is a farm that the production affected by agricultural production factors.One of the factors is cultivation technology. Effort to increase productivity of kasturi tobacco in Sumber Pinang were carried out by introducing a new cultivation guide, namely Good Tobacco Practices (GTP). Good Tobacco Practices is a general guide in carrying out the cultivation of tobacco plants correctly and appropriately, so as to obtain high productivity, good product quality, maximum benefit, and environmentally friendly. Even so, not all farmers adopt GTP. Based on this, the purpose of this study was to find out about the perceptions and motivations of GTP applicants on GTP cultivation guidelines in Sumber Pinang. The method to determining sample to find out the perceptions and motivations of farmers by using stratified random sampling which is based on the area of land cultivated by farmers. Data collection method in this study uses interview and literature study techniques. Analytical method used is using Likert scale with perceptions data analysis using attributes according to Rogers (relative advantage, level of suitability, level of complexity, can be tried, and can be observed) and motivation using attributes according to Alderfer (Existence, Relatedness, and Growth). The results of this study indicate that (1) farmers perception of GTP cultivation guidelines in Sumber Pinang is medium with good value percentage 41,1% and medium 58,9%. (2) the level of farmers motivation is high with a high percentage 67,9% and medium 32,1%.